2006
DOI: 10.1007/s10551-006-9005-9
|View full text |Cite
|
Sign up to set email alerts
|

How do Scores of DIT and MJT Differ? A Critical Assessment of the Use of Alternative Moral Development Scales in Studies of Business Ethics

Abstract: The construct of Cognitive Moral Development (CMD) has drawn much attention in the study of business ethics for over two decades. The Defining Issues Test (DIT) has made a significant contribution to the literature as an easy-to-administer CMD instrument, and the Moral Judgment Test (MJT), an alternative scale, has also been used widely especially in Europe. The two scales differ in their approaches to measuring CMD, focusing on stage preference (DIT) and stage consistency (MJT), yet empirical comparisons have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
(30 reference statements)
0
31
0
Order By: Relevance
“…This reflects moral reasoning at the conventional level as proposed by Kohlberg. As pointed out by a number of researchers (e.g., Ishida, 2006), most adults are in this stage, where moral reasoning is based on the expectations of others and norms and regulations of the society. Previous research findings on business ethics in Turkey have already demonstrated that Turkish managers closely follow ethical principles and norms (Rawwas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reflects moral reasoning at the conventional level as proposed by Kohlberg. As pointed out by a number of researchers (e.g., Ishida, 2006), most adults are in this stage, where moral reasoning is based on the expectations of others and norms and regulations of the society. Previous research findings on business ethics in Turkey have already demonstrated that Turkish managers closely follow ethical principles and norms (Rawwas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…At this level, in order to resolve moral dilemmas, individuals use universal concepts of rights and justice (Elm and Nichols, 1993). According to Kohlberg, while young children up to ages of 12 years are in stages 1 and 2, most adults are in conventional stages 3 and 4 (Ishida, 2006;) and yet ''only 20-25% of the adult population ever reaches the last two post-conventional stages'' (Ishida, 2006, p. 65). …”
Section: Self-conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advances in the work by Kohlberg and his associates, Rest and his associates, and others, the measurement of an individual's moral decision process, particularly in a business setting, could be enhanced further (Elm and Weber, 1994;Ishida, 2006;Marnburg, 2001). Most relevant to this work is the belief that individual reasoning is a dynamic process that should be reflected in a complex (not simple) and multivariate (not single) measure.…”
Section: Moral Reasoning Theorymentioning
confidence: 99%
“…Based on these theoretical foundations, instruments were developed to aid scholars seeking to measure an individual's MR processes: Moral Judgment Interview (Colby and Kohlberg, 1987), group-administered Moral Judgment Interview (Gibbs et al, 1982), Adapted Moral Judgment Interview (Weber, 1991), Defining Issues Test (Rest, 1986), revised scoring for the Defining Issues Test (Rest et al, 1997), Moral Judgment Test (Linn, 1998), Managerial Moral Judgment Test (Loviscky et al, 2007), and Multidimensional Ethics Scale (Robin et al, 1996). Despite this plethora of promising MR instrument development, the MR field remains plagued by serious methodological weaknesses (Elm and Weber, 1994;Ishida, 2006;Marnburg, 2001).…”
mentioning
confidence: 99%